Distribution and Banding Patterns of Cepaea hortensis and C. nemoralis at Cape Ann, Massachusetts - Ralph W. Dexter (Hello World!, 1989)
There are three schools of thought concerning the origin of C. hortensis in North America. Amos Binney (1837) published the first New World record (as Helir: subglobosa) from Cape Ann, Mass., noting it was especially abundant on Salt Island. It was assumed to be an introduced species. Gould (1841) also believed it was introduced by commerce. He wrote "Helix [i.e. Cepaea] hortensis is as yet confined to some limited parts of the sea-coast as the extremities of Cape Ann and Cape Cod." The Gould-Binney report (1870) stated that it "has been undoubtedly imported to this continent, and has not as yet made great advances into the interior". W. G. Binney (1885) later placed this species in the genus Tachea, and still believed it was introduced by commerce, although by then he had some question on the matter.